Extended Long‐Term Effects of Cervical Vagal Nerve Stimulation on Headache Intensity/Frequency and Affective/Cognitive Headache Perception in Drug Resistant Complex‐Partial Seizure Patients. Issue 4 (22nd November 2016) - Pintea, Bogdan; Hampel, Kevin; Boström, Jan; Surges, Rainer; Vatter, Hartmut; Lendvai, Ilana S.; Kinfe, Thomas M.
Abstract : Objectives: Invasive vagal nerve stimulation (iVNS) is an established treatment option for drug‐resistant focal seizures and has been assumed to diminish frequent co‐incidental daily headache/migraine. However, long‐term effects on cognitive/affective head pain perception, headache intensity/frequency are lacking. We therefore investigated potential iVNS‐induced effects in patients with drug‐resistant focal seizure and daily headache/migraine. Materials and Methods: A clinical database was used to select 325 patients with drug‐resistant epilepsy treated by either iVNS plus best medical treatment (BMT) or BMT alone, compared to a healthy control group (HC). We assessed headache intensity (VAS), headache frequency, affective/cognitive pain perception (PASS; FSVA), migraine disability scores (MIDAS), sleep architecture (PSQI), depressive symptoms (BDI), and body weight (BMI). Results: Nineteen patients with daily headache/migraine composed the clinical groups (10 iVNS and 9 BMT; iVNS mean age 49 years, range 36–61 years; BMT mean age 45 years, range 23–63 years; equally distributed gender). Cervical iVNS was applied from 5–13 years (mean 8 years) with following stimulation patterns: 1.3 mA (0.5–2 mA), 20 Hz, 250 μsec, 30 sec on/1.9 min off (0.5–5 min). The iVNS group had significantly lower VAS scores (iVNS 5.4; BMT 7.8; p = 0.03) and PASS cognitive/anxiety subscores (iVNS 21; BMT 16; p = 0.02) compared to BMT and HC. Global PASS ( p = 0.07), FSVA, PSQI, BDI, and BMI scores did not differ significantly between groups. Conclusions: iVNS appears to have positive modulatory long‐term effects on headache and affective/cognitive head pain perception in patients with drug‐resistant focal epilepsy, thus deserving further attention.